Analisis Pengetahuan Siswa Sebagai Upaya Mitigasi Bencana Gempa Bumi - Syakira, Salsabila; Susilawati; Vinanda, Firda; Ningtias, Afri; Mawarni, Dwiyana; Siregar, Salwa Muthiah; Rambe, Yuskaini Hadijah; Andini, Zahra (Poltekkes Kemenkes Kupang, 2024)
Background: An earthquake is an event characterized by shaking of the earth, caused by collisions between earth plates, fault activity, volcanic activity, or rock falls. This type of disaster is destructive, can occur suddenly and last for a short time. The threat of earthquake hazards can be found in almost all regions of the Indonesian Archipelago, from small to large scales that can cause damage. Objective: This research aims to examine the need for education and training as an effort to manage disasters in schools by providing guidance in documenting the hazards faced. Method: The method used is descriptive research, namely describing the results of research related to Student Knowledge as an Effort to Mitigate Earthquake Disasters. Results: Based on the results of the analysis that has been carried out, it can be seen that this study shows that the majority of students at SMP Negeri 6 Percut Sei Tuan have good knowledge about the causes of earthquakes, with (94.3%) respondents understanding that earthquakes are caused by tectonic processes due to the movement of the earth's crust or plates. This shows that students have a fairly good understanding of the basic aspects of earthquakes.